2016
DOI: 10.1111/add.13473
|View full text |Cite
|
Sign up to set email alerts
|

Estimating met demand for alcohol and other drug treatment in Australia

Abstract: Between 202 168 and 232 419 Australians are estimated to have received alcohol and other drug treatment in 2011-12. The comprehensive approach used to calculate this estimate, combining multiple independent data sets across treatment settings and programmes, can be replicated in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…In 2011/12, it is estimated that between 202, 168 and 232, 419 Australians received alcohol and other drug treatment (AOD) (Chalmers, Ritter, & Berends, 2016).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011/12, it is estimated that between 202, 168 and 232, 419 Australians received alcohol and other drug treatment (AOD) (Chalmers, Ritter, & Berends, 2016).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…pharmacological detoxification, psychosocial interventions) and are delivered through a range of public and private service providers (Chalmers et al, 2016). While supporting evidence varies across modalities, there is widespread agreement that individuals who engage with treatment services are more likely to significantly reduce or cease drug use and remain drug free than those who do not undertake treatment (Corsi, Lehman, & Booth, 2009;Madras et al, 2009;Maremmani, Pani, Pacini, & Perugi, 2007;World Health Organisation, 2008).…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%
“…Recognising the methodological problems associated with treatment counts, Chalmers and Ritter estimated that in any one year the total number of Australians in receipt of treatment ranges from 141,938 to 236,878 (Chalmers & Ritter, 2014). This is consistent with previous work (Fischer et al, 2012;Roxburgh & Degenhardt, 2008 …”
Section: Alcohol and Other Drug Treatmentsupporting
confidence: 78%
“…They found that 58% of all general practitioner encounters for drug use, excluding opioid substitution, are due to AUD and a further 8% are due to medicinal (prescribed) drug use disorders (Chalmers & Ritter, 2014).…”
Section: General Practitioner Encountersmentioning
confidence: 99%
“…Chalmers et al address the challenge of estimating the number of unique individuals receiving alcohol and other drug treatment (AOD) in Australia in a single year. As in many countries, the Australian AOD treatment system is comprised of multiple inter‐related subsystems with varying mechanisms for recording ‘treatment encounters, episodes of care, and consultations’.…”
mentioning
confidence: 99%